2017
DOI: 10.1164/rccm.201601-0083oc
|View full text |Cite|
|
Sign up to set email alerts
|

A Multicenter Randomized Trial Assessing the Efficacy of Helium/Oxygen in Severe Exacerbations of Chronic Obstructive Pulmonary Disease

Abstract: Heliox improves respiratory acidosis, encephalopathy, and the respiratory rate more quickly than air/O but does not prevent NIV failure. Overall, the rate of NIV failure was low. Clinical trial registered with www.clinicaltrials.gov (NCT 01155310).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 18 publications
0
24
0
7
Order By: Relevance
“…For example, a Cochrane review (Rodrigo et al, 2002) concluded that current evidence is insufficient to support the use of HeO 2 mixtures in the treatment of acute exacerbations of COPD and future controlled trials are advocated. Recently, a large trial (16 intensive care units, 6 countries) found that HeO 2 improves respiratory acidosis, encephalopathy and respiratory rate more quickly than Air/O 2 for COPD patients but does not prevent NIV failure (Jolliet et al, 2016). In (Häussermann et al, 2015) healthy controls, moderate to severe asthmatic and COPD patients inhaled HeO 2 during exercise.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a Cochrane review (Rodrigo et al, 2002) concluded that current evidence is insufficient to support the use of HeO 2 mixtures in the treatment of acute exacerbations of COPD and future controlled trials are advocated. Recently, a large trial (16 intensive care units, 6 countries) found that HeO 2 improves respiratory acidosis, encephalopathy and respiratory rate more quickly than Air/O 2 for COPD patients but does not prevent NIV failure (Jolliet et al, 2016). In (Häussermann et al, 2015) healthy controls, moderate to severe asthmatic and COPD patients inhaled HeO 2 during exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, international guidelines rightly recommended NIV as the first-line therapy for patients with AHRF 3,4. Several authors have carefully advised an escalation to endotracheal intubation in the case of persistent respiratory acidosis after a first NIV challenge 57. Others have recently tested extracorporeal CO 2 removal membrane after a first NIV trial that had failed to reverse hypercapnic acidosis 8,9.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Most previous studies have examined the use of heliox in non-intubated subjects who were breathing spontaneously or with the support of noninvasive ventilation. [7][8][9][10][11] A review of studies involving subjects with acute asthma concluded that breathing heliox appeared to improve pulmonary function but had no effect on the rate of hospital admission. 7 Instead of simply breathing heliox, the latter can also be used to deliver bronchodilators by nebulization.…”
Section: Introductionmentioning
confidence: 99%
“…9 The use of heliox in subjects with exacerbations of COPD who required noninvasive ventilation has been evaluated in 2 large, multi-center randomized trials. 10,11 The first study found that heliox had no significant effect on arterial blood gases or the need for intubation. 10 In the second study, subjects who received heliox had a more rapid improvement in respiratory acidosis and encephalopathy, but their rates of intubation and mortality were no different from the rates of those who were treated with standard noninvasive ventilation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation